Phosphoinositide 3-Kinase Inhibitor-Induced Hyperglycemia - Shey, Susan (J Endocr Soc, 2021)
Background: Phosphoinositide 3-kinase inhibitors (PI3Ki) are a new class of medications used to treat HR positive, HER2 negative, PIK3CA mutated advanced or metastatic breast cancer. Inhibition of PI3K, a key enzyme in the insulin signaling pathway, leads to disruption of glucose metabolism and frequently hyperglycemia. Here we present a case of difficult to treat PI3Ki-induced hyperglycemia from alpelisib. Case: 78 yo woman with metastatic breast cancer and NASH cirrhosis was referred for new hyperglycemia after starting alpelisib. Baseline HbA1c was 6%. She was initially started on metformin and glipizide without any blood glucose (BG) improvement. After 6 days, alpelisib was held with BG recovery. Alpelisib was restarted 1 month later, again resulting in hyperglycemia. Dapagliflozin treatment quickly improved BG to <200 mg/dL, but she developed candida intertrigo so it was discontinued and insulin was started. She also began a ketogenic diet. After 2 weeks of insulin titration, she had stable BG <200 on 47u of insulin a day. Within days, she was admitted with encephalopathy and a UTI which improved with antibiotics and lactulose. Alpelisib, initially held, was restarted on day 2 resulting in worsening hyperglycemia. Inpatient BG ranges on alpelisib were: fasting 191–358, pre-lunch 260–383, pre-dinner 308–404, and bedtime 330–355, despite a rapid increase of basal-bolus insulin and initiation of metformin, pioglitazone, and a ketogenic diet. Total daily insulin needs went from 18u, to 124u by day 5 of alpelisib. Imaging revealed new bone and hepatic metastases. With difficult to control hyperglycemia and cancer progression, alpelisib was discontinued with rapid improvement of hyperglycemia. Discussion: Hyperglycemia is a common adverse and on target effect of PI3Ki use. PI3K inhibition leads to acute hyperglycemia within hours. The pancreas responds by increasing insulin release. Transient hyperglycemia can occur in all patients, but may become persistent with underlying insulin resistance, as seen in our patient. T2DM (with HbA1c >6.5%) and all T1DM patients were excluded in alpelisib trials yet diabetes is not a formal contraindication. Providers should be vigilant for this complication in patients with diabetes and prediabetes. It has been suggested that exogenous insulin and medications that increase endogenous insulin secretion may be counterproductive because they overcome PI3Ki-induced insulin signaling disruption and compromise anti-tumor effectiveness of PI3Ki. Thus, the preferred and most effective treatment may be an SGLT2i as was the case in our patient. Insulin sensitizers and a ketogenic diet can potentially also be effective. Increasing insulin may have limited efficacy as seen with our patient. Future studies are needed to determine the best way to manage PI3Ki-induced hyperglycemia and the effect of potential treatments on anti-tumor efficacy.